2013
DOI: 10.1371/journal.pone.0080626
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Prevalence of Malaria Infection in Children Living in Houses with Window Screening or Closed Eaves on Bioko Island, Equatorial Guinea

Abstract: BackgroundPrevious studies demonstrated that fewer mosquitoes enter houses which are screened or have closed eaves. There is little evidence about the effect on malaria infection in humans that changes in house construction may have. This study examines the impact of protective housing improvements on malaria infection on Bioko Island.Methodology/Principal FindingsData from the annual malaria indicator surveys between 2009 and 2012 were used to assess trends in housing characteristics and their effect on RDT c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
70
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(77 citation statements)
references
References 29 publications
7
70
0
Order By: Relevance
“…Moreover in RoC, ACTs are easily accessible and affordable, as can be concluded from the fact that 31% of children presented to hospital after antimalarial self‐medication. A similar (6–13%) drop in malaria prevalence occurred in other endemic sub‐Saharan countries such as Gabon, Cameroon, Equatorial Guinea, Ghana, Burkina Faso, Kenya, Tanzania and Ethiopia . Children suffering from uncomplicated P. falciparum malaria in the study were treated according to the national treatment policy of RoC, where the recommended first‐line antimalarial is artemether–lumefantrine .…”
Section: Discussionmentioning
confidence: 77%
“…Moreover in RoC, ACTs are easily accessible and affordable, as can be concluded from the fact that 31% of children presented to hospital after antimalarial self‐medication. A similar (6–13%) drop in malaria prevalence occurred in other endemic sub‐Saharan countries such as Gabon, Cameroon, Equatorial Guinea, Ghana, Burkina Faso, Kenya, Tanzania and Ethiopia . Children suffering from uncomplicated P. falciparum malaria in the study were treated according to the national treatment policy of RoC, where the recommended first‐line antimalarial is artemether–lumefantrine .…”
Section: Discussionmentioning
confidence: 77%
“…An increase in the presence of household openings, such as windows and open eaves, has been associated with increases in mosquito entry into the home and parasite prevalence. [4][5][6][7] Poor-quality household construction materials have also been associated with increased mosquito entry, malaria incidence, and parasite prevalence. 4,5,[8][9][10][11] Several studies classify housing structures into quality groupings according to the composition of the construction materials have found poor house quality to be associated with greater presence of mosquitoes in the home and higher malaria incidence.…”
Section: Introductionmentioning
confidence: 99%
“…24 An interesting finding in this study was the association between an increase in the number of openings in the room where the study participant slept (presence of windows or eaves) and a lower incidence of malaria, which is contradictory to the findings from several other studies. [4][5][6]22,23,25 Indeed, conventional wisdom would suggest that more openings would lead to a higher mosquito density and an increased risk of malaria. In a randomized controlled trial from the Gambia, full or ceiling screening was associated with a reduction in vector density and childhood anemia, but had no effect on the prevalence of malaria infection.…”
mentioning
confidence: 99%
“…Since the establishment of a link between malaria and mosquito [11], house screening has been one of the rst experiments used as part of malaria vector control management [23]. Recent studies using house screen have found a reduced number of mosquitoes entering the house and a consequent protection of the households against mosquito bites compared to houses without screen [18,24,25]. In addition to the house screening, other studies demonstrated that well-built house with fewer entry points for mosquitoes or speci c modi cations of house design can help reducing malaria transmission by lowering human exposure to infectious bites [26,27].…”
Section: Discussionmentioning
confidence: 99%